An Urban Horizontal Expansion and Its Effect on Rural Community Livelihood: The Case of Sheger City (Oromia Special Zone Surrounding Finfinne OSZSF) Towns and Addis Ababa City Administrations Continuum Areas - Godale, Giorgis; Baraki, Goitom Abireha (Journal of Urban Development Studies, 2023)
This study focus on assessing and analyzing the Urban Horizontal Expansion and Its Effect on Rural Community Livelihood in the Oromia Special Zone Surrounding Finfinne (OSZSF) Towns and Addis Ababa City. The proposed methodology basically adopts a multiple case study research approach taking the cases of selected peri urban areas of Sheger and Addis Ababa city administrations that had continuum to boundaries of Sheger city administration Methodologically, the study take the urban fringe areas from both sides that mean from Addis Ababa city government spatial boundary perspective and from that Sheger city adminstrations (Sebeta, Burayu, Akaki, Koye Feche and Laga Tafo areas) that had direct boundary contact to the city of Addis Ababa.The results of the study indicated that compensation schemes envisaged for the loss of assets excluded youth and women. The dislocation program implemented is not rehabilitative and negatively affected the livelihood of the dislocated farming community. Furthermore, the study revealed that women and children are major victims to livelihood crisis. The coping mechanism/strategy adopted by the majority of the dislocated farmers is casual that is directly or indirectly dependent on agriculture, which is being vanished in the area. Dislocation program that may be proposed in the future needs comprehensive planning and implementation to ensure community participation and create alternative livelihood. Over the last two decades there is rapid Land use land cover change in the former Oromia special zone surrounding Finfine which is recently re-named as Sheger city administration. In this area there was very fast growth of urban built up area of which majority of them were occupied in informal ways and resulted in rapid land use land cover change in the last 20 years. The rapid built up area expansion has brought the rapid conversion of the land use and land cover from vegetation and agriculture towards urban built up area. Therefore, to succeed a sustainable urban development program, this study recommendations are the governments provide the expansion of rural area infrastructure, create job opportunity, and create awareness for rural society; and there should exist effective mechanisms for increasing agricultural productivity within a limited land size to farmers., to implement a comprehensive government's policies, challenges, and future actions required to integrate and balance the development of urban region infrastructure. Furthermore, addressing the growing socioeconomic and infrastructure gap between urban and rural sections of an urban region and in achieving the government's development plan's objectives of integrated and balanced development in OSZSF towns and Addis Ababa City.